Conditional Lempel-Ziv complexity and its application to source coding theorem with side information - Uyematsu, T.; Kuzuoka, S. (2003 IEEE International Symposium on Information Theory, 2003)
This paper proposes the conditional LZ complexity and analyzes its property. Especially, we show an inequality corresponding to Ziv's inequality concerning a distinct parsing of a pair of sequences. Further, as a byproduct of the result, we show a simple proof of the asymptotical optimality of Ziv's universal source coding algorithm with side information.